The Influence of Corporate Governance, Audit Quality, and Investment Decisions on Firm Performance in the Chemical Manufacturing Industry Subsector in Indonesia - Risa Alex Wibowo; Muhammad Ismi Hizana; Henny Setyo Lestari; Susy Muchtar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aimed to analyze the influence of corporate governance, audit quality, and investment decisions on the performance of manufacturing companies in the basic and chemical industries sub-sectors listed on the Indonesia Stock Exchange for the period 2020–2024. The research sample consisted of 23 companies selected using the purposive sampling method. Data were obtained from audited financial statements and annual reports, analyzed using panel data regression (FEM and REM) through the E-views 9 application, and considered the potential for endogeneity in the model. The results showed that the size of the board of directors had no effect on the company's performance, while the participation of women on the board had a significant positive influence on performance (ROA, ROE, and ROS). Board size has no effect on ROA and ROS, but has a significant negative effect on ROE. Audit quality, leverage, liquidity, fixed assets, and intangible assets had no effect on ROA and ROE, while company size had a significant positive influence on all three performance indicators. Investment decisions are proven to have no effect on the company's performance. The implication of this research is the importance of increasing regulation and supervision of corporate governance, especially in strengthening the role of women on the board of directors. The government is advised to continue to encourage good governance practices in this sector as a long-term strategy to maintain the stability and sustainability of corporate financial performance